Mechanical field assisted additive manufacturing of ultrahigh strength aluminum alloy - Wenjie Liu; Shengnan Shen; Jinlong Meng; Jiafeng Xiao; Hui Li; Hejun Du; Qianxing Yin; Chaolin Tan (International Journal of Extreme Manufacturing)
Additive manufacturing of aluminum (Al) alloys has attracted significant attention in the aerospace industry. However, achieving ultrahigh-strength (>500 MPa) Al alloys remains challenging due to their intrinsic poor printability. Here, we report a novel hybrid additive manufacturing (HAM) approach to process ultrahigh-strength AlMgSc alloy, which combines laser powder bed fusion (LPBF) with interlayer ultrasonic shot peening (USP). The results show that the interlayer ultrasonic shot peening depth reached ∼700 µm, leading to almost full density and residual stress convection from tension to compression. The HAM method promotes equiaxed grain formation and refines grain due to grain recrystallizations. Interestingly, the HAM followed by aging treatment tailors the hierarchically multi-gradient structures, inhibits Mg element intragranular segregation, and promotes the multi-nanoprecipitates (e.g. Al _3 (Sc, Zr) and Al _6 Mn) precipitation. Remarkably, the HAM followed by aging treatment achieves yield strength of 609 MPa and breaks elongation of 7.5%, demonstrating ultrahigh strength and good ductility compared with other Al alloys manufactured by AM and forging as reported in the literature. The strength enhancement mechanisms in this AlMgSc alloy are discussed. The high-density Al _3 (Sc, Zr) precipitates are the main strengthening contributor, and unique hetero-deformation induced (HDI) strengthening (originates from the heterogeneous microstructures) further enhances the strength of the material. This work highlights a novel approach for processing complex-structured ultrahigh strength Al alloy components by hybrid additive manufacturing.